2022
DOI: 10.1109/access.2022.3142430
|View full text |Cite
|
Sign up to set email alerts
|

Fog-RAN Enabled Multi-Connectivity and Multi-Cell Scheduling Framework for Ultra-Reliable Low Latency Communication

Abstract: Ultra-Reliable Low Latency Communication (URLLC) is a newly introduced service class targeting emerging Internet-of-Things (IoT) application scenarios. This paper assumes an interferencelimited Fog Radio Access Network (F-RAN) setup composed of multiple Remote Radio Heads (RRHs) equipped with multiple antennas serving single-antenna users. F-RAN facilitates collaborative solutions while reducing delay by pushing the network capabilities beyond the edge. By leveraging diversity, RRHs may cooperate through silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…However, the deployment of dense F-APs at the edge of the network exacerbated the degree of interference between adjacent F-APs as the network throughput increases. To solve the above problems, Kharel et al [13] analyzed the change in the throughput performance when utilizing distributed F-APs for joint transmission in an F-RAN with limited interference. Experiment results showed that the F-AP joint transmission scheme significantly improves the transmission reliability and reduces transmission delays.…”
Section: Throughput Optimization Strategy Based On Traditional Fog Ar...mentioning
confidence: 99%
“…However, the deployment of dense F-APs at the edge of the network exacerbated the degree of interference between adjacent F-APs as the network throughput increases. To solve the above problems, Kharel et al [13] analyzed the change in the throughput performance when utilizing distributed F-APs for joint transmission in an F-RAN with limited interference. Experiment results showed that the F-AP joint transmission scheme significantly improves the transmission reliability and reduces transmission delays.…”
Section: Throughput Optimization Strategy Based On Traditional Fog Ar...mentioning
confidence: 99%
“…where (a) comes from using (24), (b) from using the complementary CDF of h 0 , (c) from exploiting the property exp( i a i ) = i exp(a i ), and (d ) after taking the expectation over every h k . Observe that although (25)…”
Section: Rayleigh Fading Then the Receive Sinr Can Be Written Asmentioning
confidence: 99%
“…For instance, latency figures can be mainly improved by leveraging short codes and transmission time intervals [1], [5], [13], [14], edge caching/computing/slicing [2], [6], [12], [15], limitedoverhead protocols [2], [4], [16]- [18], and non-orthogonal multiple-access (NOMA) [2], [5], [19], [20]. Meanwhile, high reliability levels can be attained by exploiting diversity techniques as in multi-connectivity [4], [5], [21]- [24], data replication [17], [25], automatic repeat request protocols [5], [26], and multiple-input multiple-output (MIMO) systems [4], [5], [18], [27], as well as efficient network coding and relaying [12], [28]- [30] and space-time block codes [12], [13], [27]. A robust URLLC design may inevitably exploit several of the above technologies so that both latency and reliability metrics perform at the desired levels.…”
Section: Introductionmentioning
confidence: 99%
“…This work is motivated by the introduction of a Fog Radio Access Network (F-RAN) in next-generation mobile networks to achieve Ultra-Reliable Low-Latency Communication (URLLC) [32,33]. The massive distribution of Virtual Baseband Units (VBU) in F-RAN in the form of an access point or RRHs for interference coordination and resource management is similar to the architecture of a DBS network.…”
Section: Introductionmentioning
confidence: 99%